De’ Insidious Sanatorium - Francis, Frannelya (UiTM Sarawak, 2018)
Diploma of Nursing, Faculty of Health Sciences (NUSAS) was back with a twist of their new version of haunted hospital “De’ Insidious Sanatorium - Nocturnal Bete Noire”. This project attracted both the public and students from both campuses from 9 to 10 April 2018 in Blok E, Nursing Skills Laboratory. In a subtle way, with creative effects of scary sounds, make-up and logistics, the night was filled with horror, excitement and fun as participants were anxiously waiting for their turns to take part in the journey of De’ Insidious Sanatorium. Maintaining its reputation as the scariest haunted event since introduced, NUSAS obtained more positive feedbacks via social media and feedback on colored papers provided. In addition, NUSAS earned extra incomes from the ticket sales to fund the upcoming annual NUSAS dinner and future activities. This project had successfully achieved its objectives of helping students to release stress, build up good teamwork and apply entrepreneurship skills to generate income for NUSAS. NUSAS will be back with more exciting and scarier events in the future. Thank you for the endless support in our event!